Persepsi Masyarakat Terhadap Pemberdayaan Perempuan Pada Program Pnm Mekaar Dijorong Kotobaru Air Dingin Kab. Solok - Wiwi Gusmita; Solfema Solfema (Universitas Negeri Padang, 2022)
Non formal education is education that is very important to exist in the community. One form of part of education outside of school is women's empowerment which is an effort to improve the abilities and skills of women where women are always considered weak so that an empowerment is needed. There are 3 indicators in this study: 1. Financial management, 2. Timeliness 3. Borrowing rules. By using descriptive quantitative research methods. The results of this study indicate that the empowerment of women through PT PNM Mekaar can be said to have been achieved well